Internal factors that affecting financial in hotel sector (Kota Bharu) - Badri, Siti Salwa; Mohamad, Siti Wardah; Wong, Weng Kin; Yeo, Sek Jing (2015)
The objective of the research is to identify the relationship between the affecting of financial performance which is the dependent variable and well-trained, pricing tactics and technology which is independent variable. Total numbers of 150 questionnaires were distributed to 150 respondent which are working in the hotel in Kota Bharu area. 150 questionnaires were collected from the respondent for the research. According to the Pearson correlation, the relationship between the financial performance and well-trained is weak correlation co efficient of 0.245. This show that hotel financial performance is positive and related. The relationship between financial performance and pricing tactics is also show a weak relationship a weak relationship with the correlation coefficient of 0.178. This mean pricing tactics and financial performance is positive and related . There is no relationship between financial performance and technology, this how the hotel in Kota Bharu area not using the technology to improve the performance of the hotel and the technology level in the Hotel sector in Kota Bharu is low in overall.